The role of immune cells and inflammation in pulmonary hypertension: mechanisms and implications - Zhao, Hui; Song, Jialin; Li, Xiujun; Xia, Zhaoyi; Wang, Qian; Fu, Jiaqi; Miao, Yuqing; Wang, Dapeng; Wang, Xuguang (Frontiers in Immunology, 2024)
Pulmonary hypertension (PH) is a malignant disease with progressive increase of pulmonary vascular pressure, which eventually leads to right heart failure. More and more evidences show that immune cells and inflammation play an important role in the occurrence and development of PH. In the context of pulmonary vascular diseases, immune cells migrate into the walls of the pulmonary vascular system. This leads to an increase in the levels of cytokines and chemokines in both the bloodstream and the surrounding tissues of the pulmonary vessels. As a result, new approaches such as immunotherapy and anti-inflammatory treatments are being considered as potential strategies to halt or potentially reverse the progression of PH. We reviewed the potential mechanisms of immune cells, cytokines and chemokines in PH development. The potential relationship of vascular cells or bone morphogenetic protein receptor 2 (BMPR2) in immune regulation was also expounded. The clinical application and future prospect of immunotherapy were further discussed.